The Relationship of Caries of Deciduous Teeth and Physical Development of Preschool Children Living in Countryside - Musij-Sementsiv K. (Львівський клінічний вісник)
Introduction. Preschool age is an important period in the formation of the child. During this age period health and physical qualities are formed. Dynamic monitoring of children development is not only necessary for identification of the individual characteristics of harmonious development, but also it provides the diagnostic criteria for the early detection of the grounds for a more detailed examination and planning of effective preventive measures. Purpose of the study was to assess the relationship of caries of deciduous teeth and physical development of preschool children living in countryside. Materials and research methods. Groups of children were formed in a randomized way according to the age (2–6 years old), to intact and caries affected teeth, and to the different degrees of caries activity (N. V. Bidenko). To assess the physical development (height and body weight) 307 children from countryside (basic study group) and 238 children from town (control group) were examined. Results of the investigation and their discussion. During the analysis of the physical development of children of the basic and control groups it was found that their average indices correspond to the average harmonious development. Children of the basic group of research are a little taller compared with the children in the control group, but the difference is not significant. The indexes of body weight are significantly prevalent in children of the basic research group compared with the children of control group. The greatest difference was registered in children of 3-4 years of age. The three years old children weigh is 15,20 ± 0,16 kg in the basic study group and 14,50 ± 0,16 – in the control group, in four years old children – 17,46 ± 0,25 kg and 16,51 ± 0,25 kg respectively (p <0.05). Analysis of the results of research in age aspect showed that the children of the basic group aged 2-4 years with intact teeth are taller compared with the children with caries-affected teeth. However, in the control group the prevalence of height was detected in two years old children with intact teeth (93,17 ± 0,59 cm to 92,30 ± 0,78 cm), 3-4 years old children are slightly taller than the children with the caries–affected teeth. Body weight of examined children in both groups with caries of deciduous teeth was mostly greater than in healthy children. The most significant difference in body weight was observed in 3-5 years old children of the basic group. According to the analysis of physical development the growth of weight was detected in children with different degrees of caries activity. The greatest weight had children with the II and III degree of activity of caries process. The most significant difference in body weight was found in children aged 4-6. A similar trend was observed in the height of the examined preschool children. Children with the II and III degree of caries activity are taller than the children with the I degree of caries activity. The most significant difference in height was found in children aged 4-6. Conclusions. Evaluating the results, children living in countryside are slightly taller and have more weight compared with the children living in the city, especially in the age of 3-5 years. The most significant difference in terms of body weight and height is observed in children with the intact teeth and teeth affected by caries in basic study group. Analysis of anthropometric data in children of basic study group which depends on the activity of caries of deciduous teeth indicates that with increasing of the degree of carious lesions the weight and height in examined children increases as well. The most significant differences were found in children aged 4-6 years. Therefore, according to the results of research, the relationship of caries of deciduous teeth and physical development of preschool children living in countryside is observed quite informatively.